2018
DOI: 10.1159/000481813
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis Secondary to Proton-Pump Inhibitor Use

Abstract: Background: Gut dysbiosis associated with the use of proton-pump inhibitors (PPIs) has been found to lead to the occurrence of infectious and inflammatory adverse events. A longitudinal observational cohort study has demonstrated the heightened risk of death associated with PPI use. Summary: We evaluated meta-analyses to determine the association between PPI use and infectious and inflammatory diseases. Meta-analyses showed that PPI use is a potential risk for the development of enteric infections caused by Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 56 publications
1
76
1
1
Order By: Relevance
“…There is a need to observe the influence of vonoprazan on the small intestine with caution, because it was already reported that both PPI and vonoprazan induce change in intestinal bacterial flora [20]. Generally, PPI is highly beneficial for patients with acid-related disease, and their side effects are infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to observe the influence of vonoprazan on the small intestine with caution, because it was already reported that both PPI and vonoprazan induce change in intestinal bacterial flora [20]. Generally, PPI is highly beneficial for patients with acid-related disease, and their side effects are infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PPI is empirically used in clinical practice in gastroesophageal varices bleeding patients, even if there is no related evidence‐based practice. Despite its robust and rapid efficacy in acid suppression, it also has some adverse effects, including Clostridium difficile infection, pneumonia, menopausal fracture, and hepatic encephalopathy, in cirrhotic patients . For patients with cirrhosis combined with gastroesophageal reflux and peptic ulcer, the treatment strategy and duration of PPI use needs to be standardized.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that acid suppression therapy may lead to small intestinal bacterial overgrowth (SIBO), and participate in the pathogenesis of SBP. Some studies suggested that PPI therapy may be associated with SIBO and SBP …”
Section: Introductionmentioning
confidence: 99%
“…2 In recent metanalyses, PPI use was associated with a significant increase in Streptococcus and Enterococcus. 6 These changes were associated with an increased risk for the development of spontaneous bacterial peritonitis, community-acquired pneumonia, and enteric infections. Nevertheless, the exact mechanism by which these microbial community alterations affect disease susceptibility is still an active area of investigation.…”
mentioning
confidence: 99%
“…This study corroborates prior studies that reported similar increases in Streptococcus and Enterococcus species. 1,6 Since the species that were differentially increased are those often associated with the oral microbiome, the authors suggested that the increase in gastric pH as a consequence of PPI therapy may have increased bacterial migration from the oral cavity to the intestinal lumen through decreased gastric acid-related bacterial killing.…”
mentioning
confidence: 99%